Integrated analysis of Whole genome sequencing and life cycle assessment for polyhydroxyalkanoates production by Cupriavidus sp. ISTL7. (October 2021) - Gupta, Juhi; Rathour, Rashmi; Maheshwari, Neha; Shekhar Thakur, Indu
Graphical abstract: Highlights: Cupriavidus sp. ISTL7 reported 4.93 ± 0.4571 g L -1 PHA production. PHA cluster including genes phaA, phaB and phaC were revealed through WGS. LCA illustrated that PHA production with acetate + glucose was most sustainable. The production process can be improved with respect to its energy expense. Gene encoding acetoacetyl-CoA reductase was cloned, expressed and purified. Abstract: The current study demonstrates the enhanced production capability of strain Cupriavidus sp. ISTL7 for polyhydroxyalkanoates (PHA) using acetate and glucose (4.93 ± 0.4571 g L -1 ) which was characterised analytically by GC–MS, FTIR and NMR analysis. Whole genome sequencing of strain ISTL7 unveiled an array of PHA metabolism genes which included phaA, phaB and phaC. Life cycle assessment of the protocol established that the production was most sustainable with the carbon source acetate. + Glucose as compared to acetate/glucose alone. It also concluded that solvent extraction of PHA and energy consumption during the process requires optimization to sustain the production on ecological fronts. Additionally, acetoacetyl-CoA reductase (phaB) gene was molecularly cloned, expressed and purified (27 KDa, 2.63 mg/ml). Conclusively, Cupriavidus sp. ISTL7 is a potential strain for PHA production with a scope of improvement on energy fronts which would transform the production environmentally and economically appealing.